2012
DOI: 10.1038/hr.2012.51
|View full text |Cite
|
Sign up to set email alerts
|

Common variants of the UMOD promoter associated with blood pressure in a community-based Chinese cohort

Abstract: Hypertension is an important risk factor for chronic kidney disease. The kidney, in turn, has an important role in the regulation of blood pressure (BP). On the basis of a genome-wide association study, single-nucleotide polymorphisms in the uromodulin (UMOD) promoter region had been considered to influence both renal sodium reabsorption and BP. In this study, we asked whether common variants across the UMOD gene influence BP in a community-based Chinese cohort. We screened seven common variants across the UMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
(28 reference statements)
2
14
0
Order By: Relevance
“…Common variants in the promoter of the UMOD gene are linked to hypertension, CKD, and kidney stones (13)(14)(15)(16)(17). They also affect uromodulin excretion (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common variants in the promoter of the UMOD gene are linked to hypertension, CKD, and kidney stones (13)(14)(15)(16)(17). They also affect uromodulin excretion (19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the rare mutations causing ADTKD, genome-wide association studies have evidenced robust associations between common variants near the UMOD gene and urinary uromodulin levels, hypertension, eGFR, and renal function decline over time (1,(13)(14)(15)(16)(17). These common variants, which form a linkage disequilibrium block in the promoter of UMOD, are associated with increased renal expression and urinary levels of uromodulin (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…A previous case-control association study showed that G allele of rs13333226 was independently associated with a decreased risk of nephropathy, and the G allele was also associated with a higher eGFR and lower systolic blood pressure in the study cohort [27]. However, two other studies have shown that G allele carriers have higher diastolic blood pressure and higher plasma uric acid compared with A/A homozygotes [18, 19]. …”
Section: Discussionmentioning
confidence: 88%
“…Lots of studies revealed that the variants of UMOD were associated with different risk of CKD, cardiovascular disease, hypertension, and hyperuricemia, T allele of rs12917707 was associated with lower risk of CKD and ESRD [9, 10, 18, 19, 23, 24]. But the relationship between variants of UMOD and risk of kidney disease was complicated, the several rare mutation in UMOD gene has been described as a cause of uromodulin-associated kidney disease, an autosomal dominant disease [25, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation